2015
DOI: 10.4300/jgme-d-14-00424.1
|View full text |Cite
|
Sign up to set email alerts
|

Post-Code PTSD Symptoms in Internal Medicine Residents Who Participate in Cardiopulmonary Resuscitation Events: A Mixed Methods Study

Abstract: Background Internal medicine (IM) residents participate in cardiopulmonary resuscitation events (or ''codes''), stressful events that involve the death or near death of patients. Experiencing traumatic stress can lead to posttraumatic stress disorder (PTSD).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Our findings suggest that symptoms of psychological distress and ASRs are common among health professional students during the COVID-19 outbreak. As such symptoms may negatively affect job performance of healthcare workers (Kolehmainen et al, 2015) and their health if persisting (Bisson, 2019), assessment of distress may be implemented if and when the students are accelerating to the frontline. Our findings may provide first-hand evidence to help identify those who might benefit the most from family and psychological support during and after these unprecedented times.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings suggest that symptoms of psychological distress and ASRs are common among health professional students during the COVID-19 outbreak. As such symptoms may negatively affect job performance of healthcare workers (Kolehmainen et al, 2015) and their health if persisting (Bisson, 2019), assessment of distress may be implemented if and when the students are accelerating to the frontline. Our findings may provide first-hand evidence to help identify those who might benefit the most from family and psychological support during and after these unprecedented times.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the current findings, Genest et al [32] identified that following CPR, ambulance volunteers suffer from psychological impacts, such as uncontrollable, involuntary thoughts, negative feelings and recurring mental images. Mathiesen et al [33] found that CPR affected psychologically those citizens that provided it, and Kolehmainen et al [11] found that internal medicine residents reported PTSD symptoms after participating in CPR. In line with those previous findings, MDA youth volunteers that provided CPR had higher mean scores of intrusion, hyper-arousal and avoidance compared to volunteers that had not provided such procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Self-efficacy refers to the level of self-reported perceptions regarding competence to achieve one’s ambitions [10]. PTSD is a psychiatric disorder that may appear among individuals that experience a traumatic event [11,12]. Symptoms of PTSD may include intrusive thoughts like re-experiencing the traumatic events, avoidance of places and activities that may remind of the trauma or hyper-arousal, such as sleep deficiency and being overly alert [13].…”
Section: Introductionmentioning
confidence: 99%
“… 3 Risk for residents can be compounded by exposure to adverse events, such as medical errors and/or unexpected negative patient outcomes, potentially triggering trauma symptoms. 6 8 …”
mentioning
confidence: 99%
“…9 The harm experienced by traumatized hospital workers has been compared with the harm that occurs to military personnel involved in unintentional “friendly fire.” Rates of trauma symptoms among resident physicians are higher than expected in the general population, ranging from 12% to 28%. 6 8 , 10 …”
mentioning
confidence: 99%